Altered striatum centered brain structures in SHANK3 deficient Chinese children with genotype and phenotype profiling. (May 2021) - Liu, Chunxue; Li, Dongyun; Yang, Haowei; Li, Huiping; Xu, Qiong; Zhou, Bingrui; Hu, Chunchun; Li, Chunyang; Wang, Yi; Qiao, Zhongwei; Jiang, Yong-hui; Xu, Xiu
Highlights: The copy number variation of SHANK3 contributes 0.4 % to Chinese children with ASD. Comprehensive clinical, neurobehavioral, and brain imaging assessments were reported in SHANK3 deficient Chinese children. SHANK3 -deficient ASD patients relate to the disrupted striatum centered connectivity. Abstract: SHANK3 deficiency represents one of the most replicated monogenic risk factors for autism spectrum disorder (ASD) and SHANK3 caused ASD presents a unique opportunity to understand the underlying neuropathological mechanisms of ASD. In this study, genetic tests, comprehensive clinical and neurobehavioral evaluations, as well as multimodal structural MRI using voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) were conducted in SHANK3 group (N = 14 with SHANK3 defects), ASD controls (N = 26 with idiopathic ASD without SHANK3 defects) and typically developing (TD) controls (N = 32). Phenotypically, we reported several new features in Chinese SHANK3 deficient children including anteverted nares, sensory stimulation seeking, dental abnormalities and hematological problems. In SHANK3 group, VBM revealed decreased grey matter volumes mainly in dorsal striatum, amygdala, hippocampus and parahippocampal gyrus; TBSS demonstrated decreased fractional anisotropy in multiple tracts involving projection, association and commissural fibers, including middle cerebral peduncle, corpus callosum, superior longitudinal fasciculus, corona radiata, external and internal capsule, and posterior thalamic radiation, etc. We report that the disrupted striatum centered brain structures are associated with SHANK3 deficient children. Study of subjects with monogenic cause offer specific insights into the neuroimaging studies of ASD. The discovery may support a path for future functional connectivity studies to allow for more in-depth understandings of the abnormal neural circuits and the underlying neuropathological mechanisms for ASD.